Pengaruh Independensi, Komitmen Organisasi dan Pemahaman Good Government Governance Terhadap Kinerja Auditor (Studi pada Badan Pengawas Keuangan dan Pembangunan Perwakilan Provinsi Jambi) - Azza Kasni; Afrizal Afrizal; Ilham Wahyudi (Magister Ilmu Akuntansi Universitas Jambi, 2018)
This study aims to examine the effect of independence, organizational commitment, and understanding of good government governance on BPKP Representative Jambi Province auditor’s performance partially and simultaneously. The sample of this research is all auditors at BPKP representative of Jambi Province with total sampling technique. The type of research data is ordinal data obtained by distributing questionnaire, transformed into interval data by MSI method. The result of the research shows that partially, the auditor’s independence variable and organizational commitment have positive and significant effect to auditor’s performance, while the understanding of good governance partially has no effect on auditor performance. While simultaneously, the variable of auditor independence, organizational commitment, and understanding of good governance together have a positive and significant effect on auditor performance. Keywords: Independence, Organizational Commitment, Understanding Good Government Governance, Auditor’s Performance